(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study investigates the relationship between swimming and endurance capacity through a systematic literature review. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to ensure a transparent and structured selection process. Articles published between 2010 and 2025 were retrieved from Scopus, PubMed, Google Scholar, and ScienceDirect using keywords related to swimming, endurance, aquatic exercise, and aerobic capacity. After applying the inclusion and exclusion criteria, six studies were included in the final qualitative synthesis. Data were analyzed using qualitative thematic synthesis by comparing study characteristics, intervention models, training duration and frequency, participant profiles, and endurance outcomes such as VO₂ max, 6-minute walk test performance, heart rate response, and swimming time trials. The findings indicate that swimming contributes positively to cardiorespiratory and muscular endurance in athletes, older adults, and recreational participants. Structured swimming programs, particularly those involving progressive intensity, interval training, and aquatic resistance components, tended to produce stronger endurance adaptations. However, the review is limited by methodological heterogeneity, small sample sizes in several studies, inconsistent endurance measurements, and limited long-term evidence. Future research should employ standardized testing protocols, longitudinal designs, and broader participant groups. Overall, swimming can be considered an effective, low-impact, and adaptable method for improving endurance capacity.